Handbook of New Age - Kemp, Daren.; Lewis, James R. (Brill handbooks on contemporary religion, 2007)
The Handbook of New Age is a comprehensive survey of alternative spiritualities: their history, their global impact, their cultural influence and how they are understood by scholars. Chapters by many of the leading scholars of the movement give the latest analysis of contemporary spiritual trends, and present up-to-date observations of the interaction between the New Age movement and many different fields of knowledge and research.